Trends of Steroids in the Youth (Global Journal of Medical Research, 2013)
Anabolic steroid usage has been recognized as a serious health and ethical problem in youth for several decades. Numerous examples of steroid usage rules violations have been highly publicized and have lead to the suspension .Youth, however, are not the only population of individuals that use steroids. The objective of this article is to determine the usage of steroids in the youth as a trend and to compare our findings with survey that why steroids are consumed and what are the advantages and disadvantages and also acknowledgement. To measure these attitudes, we conducted a survey of 200 people from different gyms. More than (83.5 %) percent of the study group reported that they heard about current or previous anabolic steroid usage. According to the previous eighty-eight (88%) percent had heard of anabolic steroids, but only 59.5% had heard their side effects explained to them. In survey, 88% had heard of anabolic steroids, 59.5% had heard the side effects explained to them, and 19.5% admitted to using steroids. 24.5% said that steroids should be promoted. Only 16.5% says that steroids are healthy and 29.5 % think that a steroid improves muscles and strength. Only 18.5% take steroids as a pain reliever. These results suggest that anabolic steroids remain a problem among young. Educational programs should be instituted during junior high school to increase the knowledge of anabolic steroids in this group. Information should come from qualified individuals including coaches, teachers, trainers, and especially parents.